Osmotic coefficients and apparent molar volumes of 1-hexyl-3-methylimidazolium trifluoromethanesulfonate ionic liquid in alcohols - Emilio J. González (2014)
In this work, density for the binary mixtures of 1-hexyl-3- methylimidazolium trifluoromethanesulfonate in alcohols (1-propanol, or 2-propanol, or 1-butanol, or 2-butanol, or 1-pentanol) was measured at T = 323.15 K and atmospheric pressure. From this property, the corresponding apparent molar volumes were calculated and fitted to a Redlich-Meyer type equation. For these mixtures, the osmotic and activity coefficients, and vapor pressures of these binary systems were also determined at the same temperature using the vapor pressure osmometry technique. The experimental osmotic coefficients were modeled by the Extended Pitzer model of Archer. The parameters obtained in this correlation were used to calculate the mean molal activity coefficients and the excess Gibbs free energy for the studied mixtures.